(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to identify the impact of digital transformation on improving employee service quality among employees in the Saudi telecommunications sector in Jeddah. A descriptive and analytical approach was adopted. The study population consisted of employees in the Saudi telecommunications sector in Jeddah. The sample was randomly selected, and (190) responses were obtained. A questionnaire was used to collect data using the statistical analysis program (SPSS). The study results indicated that the study sample members perceived a very high level of digital transformation in the Saudi telecommunications sector in Jeddah. The study results also indicated that the study sample members perceived a very high level of employee service quality among employees in the Saudi telecommunications sector in Jeddah. The study results demonstrated a positive and statistically significant impact of digital transformation on improving employee service quality in the Saudi telecommunications sector in Jeddah. The study recommends the design and implementation of specialized training programs aimed at enabling employees to use modern digital technologies efficiently, which contributes to enhancing the speed of response and reliability in service delivery.